Children Under Wars Rehabitilation Center - Bára, Sara (My University, 2017)
Children care center specially for those who witness wars & it's effects to help them overcome this trauma through a child friendly healing environment. Concept : The main idea is to create a child friendly environment to simulate child world and his imagination to encourage him to discover it so be healed . Main Key words to describe the project environment : ( Family Environment(homey/cozy) /Safety/ Free to use & discover the place /Social interaction / Visual Continuity/Play Based Functions /Open to Nature /No boundaries but under control ). So I use a popular element to the child which is ( Tree House ) to create the whole environment . [A cluster of tree house unit to create a micro children city like ].